Continuation of Anti-TNF in Patients With Ulcerative Colitis in Remission Is Not Cost-effective Compared With Treatment Withdrawal: A Markov Model. (30th October 2020) - Mahmoud, Remi; van Lieshout, Chris; Frederix, Geert W J; Jharap, Bindia; Oldenburg, Bas
Abstract: Background and Aims: Anti-tumour necrosis factor alpha [anti-TNF] treatment accounts for 31% of health care expenditures associated with ulcerative colitis [UC]. Withdrawal of anti-TNF in patients with UC in remission may decrease side effects and infections, while promoting cost containment. Approximately 36% of patients relapse within 12–24 months of anti-TNF withdrawal, but reintroduction of treatment is successful in 80% of patients. We aimed to evaluate the cost-effectiveness of continuation versus withdrawal of anti-TNF in patients with UC in remission. Methods: We developed a Markov model comparing cost-effectiveness of anti-TNF continuation versus withdrawal, from a health care provider perspective. Transition probabilities were calculated from literature, or estimated by an expert panel of 11 gastroenterologists. Deterministic and probabilistic sensitivity analyses were performed to account for assumptions and uncertainty. The cost-effectiveness threshold was set at an incremental cost-effectiveness ratio of €80, 000 per quality-adjusted life-year [QALY]. Results: At 5 years, anti-TNF withdrawal was less costly [-€10, 781 per patient], but also slightly less effective [-0.04 QALY per patient] than continued treatment. Continuation of anti-TNF compared with withdrawal costs €300, 390/QALY, exceeding the cost-effectiveness threshold. Continued therapy would become cost-effective if the relapse rate following anti-TNF withdrawal was ≥43% higher, or if adalimumab or infliximab [biosimilar] prices fell below €87/40 mg and €66/100 mg, respectively. Conclusions: Continuation of anti-TNF in UC patients in remission is not cost-effective compared with withdrawal. A stop-and-reintroduction strategy is cost-saving but is slightly less effective than continued therapy. This strategy could be improved by identifying patients at increased risk of relapse.